2022
DOI: 10.26599/bdma.2022.9020010
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors and Clustering Characteristics of COVID-19: A Global Analysis

Abstract: The unprecedented coronavirus disease 2019 (COVID-19) pandemic is still raging (in year 2021) in many countries worldwide. Various response strategies to study the characteristics and distributions of the virus in various regions of the world have been developed to assist in the prevention and control of this epidemic. Descriptive statistics and regression analysis on COVID-19 data from different countries were conducted in this study to compare and evaluate various regression models. Results showed that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Task Accuracy User Experience Task Efficiency N/A [14,16,18,22,24,[27][28][29][30][32][33][34][35][37][38][39][41][42][43][44][45][46][47]49,[52][53][54][55][56][57][58][59]61,64,65,[68][69][70]72,73,[75][76][77][78][79][81][82][83][84][85][86][87]…”
Section: Papers Standard Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…Task Accuracy User Experience Task Efficiency N/A [14,16,18,22,24,[27][28][29][30][32][33][34][35][37][38][39][41][42][43][44][45][46][47]49,[52][53][54][55][56][57][58][59]61,64,65,[68][69][70]72,73,[75][76][77][78][79][81][82][83][84][85][86][87]…”
Section: Papers Standard Methodologymentioning
confidence: 99%
“…With regard to datasets, 72.81% (83/114) of the studies indicated which ones they used. However, owing to the extent and variety of the studies reviewed, there were only eight duplicate sources: Korea Centers for Disease Control & Prevention (KCDC) [30,44,71,106,107], Johns Hopkins University datasets [15,23,28,42,46,47,53,57,75,81,[84][85][86]95,97,98,125], WHO COVID-19 Daily Report [30,42,43,76,102], European Centre of Disease Prevention and Control (ECDC) [57,86,100,108,118], Centre of Disease Prevention and Control (CDC) on COVID-19 [24,30,31,55,95,102], the National Health Commission [42,43,52,55,87], the US Census Bureau [31,46,49,…”
Section: Papers Standard Methodologymentioning
confidence: 99%
See 3 more Smart Citations